Nonisothermal crystallization kinetic study and thermal stability of multiwalled carbon nanotube reinforced poly(phenylene sulfide) composites - Ribeiro, B. [UNESP]; Hein, L. R.O. [UNESP]; Costa, M. L. [UNESP]; Pötschke, P.; Burkhart, T.; Botelho, E. C. [UNESP] (Wiley, 2017)
The aim of this work is obtain multiwalled carbon nanotube reinforced poly(phenylene sulfide) (PPS) nanostructured composites by melt mixing technique and further characterization of their morphological and thermal properties. Transmission electronic microscopy and scanning electron microscopy analysis were performed to evaluate the quality of multi-walled carbon nanotubes (MWCNT) dispersion throughout the PPS matrix. The incorporation of nanofiller in polymeric matrix was responsible for an increase in crystallinity due to heterogeneous nucleation phenomenon. In addition, Avrami, Ozawa, and Mo modeling were used to study the crystallization kinetics of MWCNT/PPS composites. It can be seen from TGA plots (thermogravimetric analysis) an increase in the maximum degradation temperature by the addition of nanofiller in polymeric matrix. POLYM. COMPOS., 38:604–615, 2017. © 2015 Society of Plastics Engineers.